Obstructive sleep apnea and bariatric surgical guidelines: summary and update. Issue 1 (February 2018) - de Raaff, Christel A.L.; de Vries, Nico; van Wagensveld, Bart A.
Abstract : Purpose of review: Increasing numbers of bariatric surgical procedures and the high prevalence of obstructive sleep apnea (OSA) in this population have resulted in a growing interest in the perioperative management of OSA in bariatric surgery. This review provides a summary of the first consensus guideline on this topic as well as an update of the newest literature available. Recent findings: All bariatric patients should be screened for OSA and obesity hypoventilation syndrome (OHS) to reduce the risk of perioperative complications. Intraoperative precautions are preoxygenation, induction and intubation in ramped position, continuous positive airway pressure (CPAP) and positive end-expiratory pressure during induction, maintenance of low tidal volumes during surgery, multimodal anesthesia and analgesia with avoidance of opioids and extubation when patients are free of neuromuscular blockage. CPAP therapy and continuous monitoring with a minimum of pulse oximetry is recommended in the early postoperative period. Summary: Multiple precautions exist to minimize the risk of cardiopulmonary complications and to enhance recovery after surgery. A combination of these procedures seems to provide optimal perioperative care of OSA patients undergoing bariatric surgery. Nearly 75% of recommendations are based on low quality of evidence, indicating the high value of experts' opinion and potential for future research.